Régner précairement: inventing precarity in Early Modern France - O'Sullivan, L (Cambridge University Press, 2024)
The language of precariousness – précaire, précairement – occupied a crucial but fiercely contested position in early modern French culture. This article traces the emergence of this concept, tracking its journey from legalistic jargon to buzzword as it is applied, co-opted, and subverted in service of the political and constitutional arguments that gripped France in the century following the outbreak of the Wars of Religion. Arguing for the significance of these largely neglected political discourses, it uncovers a conception of precarity radically unfamiliar to contemporary eyes and an early modern culture capitalising on the rhetorical potential this language affords.